The art teacher's book of lists : grades K-12 - Hume, Helen D., 1933- (San Francisco : Jossey-Bass, 2010)
'A revised and updated edition of the best-selling resource for art teachers This time-tested book is written for teachers who need accurate and updated information about the world of art, artists, and art movements, including the arts of Africa, Asia, Native America and other diverse cultures. The book is filled with tools, resources, and ideas for creating art in multiple media. Written by an experienced artist and art instructor, the book is filled with vital facts, data, readings, and other references, Each of the book's lists has been updated and the includes some 100 new lists Contains new information on contemporary artists, artwork, art movements, museum holdings, art websites, and more Offers ideas for dynamic art projects and lessons Diverse in its content, the book covers topics such as architecture, drawing, painting, graphic arts, photography, digital arts, and much more.'--
Includes bibliographical references and index
Keywords: Art -- Miscellanea